CALLITRICHE NANA (CALLITRICHACEAE), A NEW SPECIES FROM JAVA, INDONESIA - W. J.J.O. De Wilde; B. E.E. Duyfjes; B. Gravendeel; R. W.J.M. Van der Ham; B. C. Ho; Rugayah Rugayah; G. T.P. Vo (Floribunda, 2002)
Callitriche nana B.C. Ho & G.T.P. Vo, the first Callitriche species from Java, is described. It is a terrestrial species, not a terrestrial form of an aquatic species. It has the smallest stature among the some 50 species known world-wide. The species is distinct in several other morphological characters as well. Phylogenetic analyses of its rbcL sequences also indicate an isolated position in the genus Callitriche.